2000
DOI: 10.1002/(sici)1098-2736(200003)37:3<237::aid-tea2>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Ways of Knowing beyond Facts and Laws of Science: An Ethnographic Investigation of Student Engagement in Scientific Practices

Abstract: In this study, an anthropological perspective informed by sociolinguistic discourse analysis was used to examine how teachers, students, and scientists constructed ways of investigating and knowing in science. Events in a combined fourth-and fifth-grade elementary class were studied to document how the participating teacher provided opportunities for students to diverge from the intended curriculum to pursue their questions concerning the behavior of sea animals in a marine science observation tank. Analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 41 publications
0
47
1
2
Order By: Relevance
“…In this article we draw on a variety of published work, such as that of Lemke (1990;, Kress, Jewitt, Ogborn & Tsatsarelis (2001), Duval (2002;diSessa (2004), in order to craft a concept that we call disciplinary discourse (the complex of representations, tools and activities of a discipline). What we bring to earlier work is the suggestion that students need to become fluent in a critical constellation of the different semiotic resources-or modes of disciplinary discourse as we depict thembefore they can appropriately holistically experience the disciplinary way of knowing that these resources/modes potentially give access to.…”
Section: A Disciplinary Discourse Perspective On University Science Lcontrasting
confidence: 64%
See 2 more Smart Citations
“…In this article we draw on a variety of published work, such as that of Lemke (1990;, Kress, Jewitt, Ogborn & Tsatsarelis (2001), Duval (2002;diSessa (2004), in order to craft a concept that we call disciplinary discourse (the complex of representations, tools and activities of a discipline). What we bring to earlier work is the suggestion that students need to become fluent in a critical constellation of the different semiotic resources-or modes of disciplinary discourse as we depict thembefore they can appropriately holistically experience the disciplinary way of knowing that these resources/modes potentially give access to.…”
Section: A Disciplinary Discourse Perspective On University Science Lcontrasting
confidence: 64%
“…In a similar vein, a number of authors have made the case that challenges found in student learning are largely a function of difficulties in handling and understanding highly specialized forms of communication that are not found to any great extent in everyday situations, for example, Driver & Ericksson (1983), Solomon (1983), Säljö (2000), and diSessa & Sherin (2000). Learning is thus increasingly being characterized in discourse terms (for example diSessa, 2004;Florence & Yore, 2004;Lemke, 1990Lemke, , 1995Lemke, , 1998Northedge, 2002Northedge, , 2003Roth, McGinn, & Bowen, 1996;Swales, 1990;Säljö, 1999;Wickman & Östman, 2002).…”
Section: A Disciplinary Discourse Perspective On University Science Lmentioning
confidence: 80%
See 1 more Smart Citation
“…Recent studies in science have focused on the characteristics of classroom talk and questions that facilitate productive thinking in students (e.g., Abell, Anderson, & Chezem, 2000;Crawford, Kelly, & Brown, 2000;Gallas, 1995). This study contributes to the growing literature on the nature of dialogue during science instruction that facilitates student thinking.…”
Section: Significance Of Studymentioning
confidence: 99%
“…Research literature about inquiry classrooms often does not describe the classroom practices, rather classroom inquiry is summarized as ''doing science,'' ''hands-on science,'' or ''real-world science'' (Crawford, 2000). Furthermore, researchers often label a classroom as inquiry-oriented based on the nature of the curriculum materials used by the teacher and not by what the teacher and students are actually doing (Flick, 1995).…”
Section: Role Of Teachers In Inquirymentioning
confidence: 99%